The effects of the plant extract on embryonic development of zebrafish (Danio rerio) - Anita Restu Puji Raharjeng; Atika Ayu Kusumaningtyas; Dita Arya Widatama; Siti Zarah; Sandi Fransisco Pratama; Husnul Budiatman Dani (Genetikawan Muda Indonesia, 2021)
The early developmental stages of fish are particularly sensitive. Plant extract with its content can have a good or bad effect on this embryonic phase, depending on the concentration and period. The impact can range from disruption of embryonic development to death. Disorders of embryo development commonly observed are the hatching rate, delay or premature hatching, survival rate, heartbeat rate, morphological changes, and body malformations. The chorion does not fully protect the embryo against plant extract because the content of plant extract has a small specific gravity to enter and penetrate the chorion layer. The variety of plant extract contents can make the results of research less predictable so that the single material contain is felt to have a more accurate impact on natural medicine research.